A century of new orchid records in Bhutan / (Acc: D 1145) - The National Biodiversity Centre (Thimphu : The National Biodiversity Centre, 2017)
A century of new orchid records in Bhutan is a stunning visual book of all the newest orchid discoveries found in Bhutan. Each species have a visual pictutre and an artist rendering.
Keywords: Orchid records in Bhutan